DISCLOSURE AND IMPLEMENTATION OF CORPORATE SOCIAL RESPONSBILITY (CSR) INDONESIAN SHARIA BANK IN ISLAMIC RELIGIOUS INSTITUTIONS IN BUTON ISLANDS (Case Study at BSI KCP Baubau) - â€â€â€Ž â€â€â€Ž â€â€â€Ž â€â€â€Ž, La Marihi (Program Doktor Ilmu Ekonomi, 2022)
The purpose of this study was to determine the disclosure and supporting factors for the implementation of CSR BSI Baubau Unit at Islamic religious institutions in the Buton Islands. The results of this study found that CSR disclosure at BSI KCP Baubau was mostly carried out by government institutions, namely the Office of the Ministry of Religion and State Madrasah and the supporting factors for CSR implementation were due to the cooperation agreement, the availability of CSR funds, and the establishment of good communication between the BSI KCP Baubau and other institutions. the. The greater the number of civil servant customers who borrow (credit) at BSI KCB Baubau, the greater the disclosure and implementation of CSR funds at the institution concerned in the Buton Islands. Keyword: Disclosure, Support, Corporate Social Responsibility, Financial Performance.